THE EFFECT OF CORPORATE GOVERNANCE PRACTICES ON EARNINGS MANAGEMENT OF COMPANIES LISTED AT THE NAIROBI SECURITIES EXCHANGE - Iraya, Cyrus; Mwangi, Mirie; Muchoki, Gilbert W. (European Scientific Journal, ESJ, 2015)
The objective of the study was to establish the effect of corporate governance practices on earnings management of companies listed at the Nairobi Security Exchange (NSE). The target population consisted of the 49 companies that had been continuously and actively trading at the NSE between January 2010 and December 2012. Secondary data was used covering the period 2010 to 2012 and analyzed using linear regression to test the effect of the independent variables on the dependent variable. The study found that earnings management is negatively related to ownership concentration, board size and board independence but positively related to board activity and CEO duality. The study recommended the need for effective corporate governance practices in listed companies in Kenya to contribute to reduced earnings management and avert possible collapse of listed companies in Kenya.